Заброшенные особняки и Босфор: к вопросу о символических образах в романе Орхана Памука «Стамбул: город воспоминаний» - Посохова, Е.В. (Культура народов Причерноморья, 2013)
Настоящая статья рассматривает вопрос о центральных символических образах в
автобиографическом романе лауреата Нобелевской премии по литературе 2006 г. турецкого писателя
Орхана Памука. Доказано, что таковыми являются заброшенные особняки и пролив Босфор.
Исследована роль данных символических образов в формировании идейно-художественного своеобразия
романа. Доказано, что ключевой особенностью Стамбула Орхан Памук считает особого рода
коллективную печаль, источник которой усматривается в падении Османской империи. Именно образ
разрушенных особняков выражает стамбульскую печаль. Чувству грусти в романе противопоставлены
вдохновение и свобода, которые несет в себе образ Босфора. Последний позволяет примириться со
стамбульской печалью и принять ее как данность.
Ключевые слова: символических образ, Стамбул, стамбульская печаль, турецкий роман, Орхан Памук. Ця стаття розглядає питання про центральнi символічнi образи в автобіографічному романі
лауреата Нобелівської премії з літератури 2006 р. турецького письменника Орхана Памука. Доведено,
що, такими є занедбані особняки та протока Босфор. Досліджено роль цих символічних образів у
формуванні ідейно-художньої своєрідності роману. Доведено, що ключовою особливістю Стамбула
Орхан Памук вважає винятковий колективний сум, джерело якого вбачається у падінні Османської
імперії. Саме образ зруйнованих особняків виражає стамбульський сум. Цьому почуттю в романі
протиставленні натхнення і свобода, які несе в собі образ Босфору. Він дозволяє примиритися зі
стамбульським сумом і прийняти його як даність.
Ключові слова: символічний образ, Стамбул, стамбульський сум, турецький роман, Орхан Памук. The present paper focuses on the problem of the main symbolic figures in the autobiographic novel
by a Turkish writer and Nobel price winner Orhan Pamuk. It is proved that the main symbolic figures are the
ruinous mansions and Bosporus strait. The role of these symbolic figures in the formation of the idea-artistic
originality of the novel is investigated. It is proved that a special collective sorrow is considered by Orhan
Pamuk to be the key distinctive feature of Istanbul. Its source is found in the collapse of Ottoman Empire and the
further disappearance of its culture. The historical changes connected with the fall of once great empire,
metaphorically speaking, moved Istanbul away to the world periphery. That inevitably has changed the look of
the city and its atmosphere. Istanbul has become neglected and full of ruins whereas its citizens has experienced
the feeling of deep collective sorrow. It is stated that the figure of the ruinous mansions in particular represents
Istanbul sorrow in the novel. It is opposed to the inspiration and freedom expressed in the figure of Bosporus.
The latter allows to reconcile to the Istanbul sorrow and to except it as given.
Key words: Symbolic Figure, Istanbul, Istanbul Sorrow, Turkish Novel, Orhan Pamuk.